The Terms Cetiya and Thūpa with Special Reference to the Canon - Rathanapala, Mahawela (University of Sri Jayewardenepura, Nugegoda., 2015)
Both terms thūpa and cetiya are used synonymously to indicate the monuments which were built to commemorate great virtues of the Buddha. But, an analysis of the terms indicates that the Buddha used these two terms in two different contexts. There are ample of canonical references to prove that both concepts cetiya and thūpa were in usage as a very famous concept of establishing monuments in the period of the Buddha. In the Pāli Buddhist Canon, there are various statement made by the Buddha in praising the beauty of pre- Buddhist cetiya-s. Cetiya Sutta, Bhūmicālasutta and the Mahāparinibbānasutta are such instances. The term thūpa also can be seen in some sutta-s of the Pāli canon, which for instances, Bhāhiyadārūcīriyasutta of the Udānapāli and the Mahāprinibbānasutta of the DīghnikāyaCetiyasutta in the Mahāvagga of the Saṃyutanikāya explain a few of pre Buddhist monuments by names as, Vesāli, Udena, Gotamaka, Sattamba, Bahuputtaka, Sārandada and Cāpāla. The same list of names can be seen elsewhere in the Pāli Canon. But even though the term thūpa can be seen in the sutta-s, there is no a single reference in the Pāli Canon to a name or a place of a pre-Buddhist thūpa. The most famous denotations on the thūpa in the Pāli Canon is thūpārahapuggala. In the Mahāprinibbānasutta of the Dīghanikāya while the Buddha explaining the customs that should be followed in conducting his funeral, he admonishes that, the Buddha, Paccekabuddha, Arahant and the universal king are worthy of commemoration even after their death, by erecting thūpa-s on their relics. The term cetiya has been used by the Buddha to indicate the pre-Buddhist monuments, But there is no usage of term thūpa for the pre-Buddhist monument. On the other hand, the beauty of cetiya-s has been praised with their names, but there is no such indication about the thūpa in the Pāli Canon. The term thūpa has been used as a compound word as a thūpārahapuggala but there is no such indication as cetiyārahapuggala in the Canon which means terms cetiya and thūpa are used in the Pāḷi Canon in two different senses. In this study, Pāli Canon, specially Suttanta and Vinayapiṭaka are utilized as primary sources to investigate the occurrences of terms cetiya and thūpa. Relevant commentaries and sub commentaries are utilized for further analysis of terms and to discuss critically their applied contexts. Later grammatical compositions are also refereed to critically in investigating the etymology of terms cetiya and thūpa in support of the detailed exposition of facts.
Keywords: Cetiya; Thūpa; Dhātu; Suttantapiṭaka; Vinayapiṭaka; Ṛgveda